Foreign investment, corporate governance and performance in the Chinese listed a share companies - Beatson, Samuel A.; Chen, Jian (Taylor & Francis, 2018)
We present a novel lens on the presence and impact of qualified foreign institutional investors (QFII) in top shareholdings of the non-financial domestically listed Chinese ‘A’ share firms. The initial results suggest that the presence of a QFII as a top shareholder in these companies is associated with their better performance, using both Tobin’s Q and ROA as the performance measures. Our models include variables representing corporate governance mechanisms, foreign legal person shares, a proxy for international affiliations and a number of time-variant firm characteristics. Economically, the coefficient of impact on the market measure is the more significant, while the effect of having a QFII in top shareholdings on both performance measures is empirically significant. Previously, studies have often ignored the potential for reverse causality beyond using lagged regressors. This is problematic. Therefore, we follow up with a 2SLS instrumental variables and system GMM model to further mitigate this potential and find the empirical relationship holds. Contrary to earlier work on QFIIs and governance post-implementation of the QFII scheme, the findings from our models suggest that the presence of a QFII top shareholder augments market performance holding equal existing corporate governance mechanisms and other controls.